Sexual dimorphism in immunity and longevity among the oldest old - Arakelyan, Nelli A.; Kupriyanova, Daria A.; Vasilevska, Jelena; Rogaev, Evgeny I. (Frontiers in Immunology, 2025)
Human longevity is a sex-biased process in which sex chromosomes and sex-specific immunity may play a crucial role in the health and lifespan disparities between men and women. Generally, women have a higher life expectancy than men, exhibiting lower infection rates for a broad range of pathogens, which results in a higher prevalence of female centenarians compared to males. Investigation of the immunological changes that occur during the process of healthy aging, while taking into account the differences between sexes, can significantly enhance our understanding of the mechanisms that underlie longevity. In this review, we aim to summarize the current knowledge on sexual dimorphism in the human immune system and gut microbiome during aging, with a particular focus on centenarians, based exclusively on human data.